Odpowiedzi

2010-03-06T17:05:07+01:00
-0,07(10x-1)=0,3x
-0,7x + 0,07 = 0,3x
-0,7x - 0,3x = -0,07
-1x = -0,07 |: (-1)
x = 0,07


0,83x+0,82=0,23x+1,52
0,83x - 0,23x = 1,52 - 0,82
0,60x = 0,70 |: 0,60
6x = 7|: 6
x = 1 1/6

0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x + 0,2x - 0,2 = 0,2x + 0,2
0,6x + 0,2x - 0,2x = 0,2 + 0,2
0,6x = 0,4 | : 0,6
6x = 4|: 6 =
x = 4/6 = 2/3

0,7(x+2)=0,4(x+1)+0,3x+1
0,7x - 0,14 = 0,4x + 0,4 + 0,3x + 1
0,7x - 0,4x + 0,3x = 1 + 0,4 + 0,14
0,6x = 1,54 | :0,6
60 = 154|: 60
x = 2 34/60 = 2 17/30

0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x + 0,6 = 2,6 +0,6x - 0,6
0,3x + -0,6x = -0,6 + 2,6 - 0,6
-0,3x = 1,4 |: (-0,3)
-3 = 14 |: (-3)
x = -4 2/3

0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x + 0,1 - 0,15x - 0,5 = 0,4 - 0,35x
0,1x - 0,15x + 0,35 = 0,4 + 0,5 - 0,1
0,3x = 0,8 |: 0,3
x = 8|: 3
2 2/3

2010-03-06T17:16:59+01:00
1) -0,7x+0,07=0,3x całość razy 100
-70x+7=30x
-100x=-7
x=0,07
2)całość razy 100
83x+82=23x=152
60x=70
x=7/6
3)0,6x+0,2x-0,2=0,2x+0,2
0,6x=0,4
x=2/3
4)0,3x+0,7=2,6+0,6x-0,6
-0,3x=1,3
x=4 i 1/3
2010-03-06T17:47:08+01:00
-0,07(10x-1)=0,3x
-0,7x+0,07=0,3x
-0,7x-0,3x=-0,07
-x=-0,07
x=0,07
0,83x+0,82=0,23x+1,52
0,83x-0,23x=1,52-0,82
0,6x=0,7
x=0,42
0,6x+2(0,1x-0,1)=0,2(x+1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x= 0,4/:0,6
x=2/3
0,7(x+2)=0,4(x+1)+0,3x+1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x+1,4=0,7x+1,4x
równanie tożsamościowe x=R


0,15(2x+4)=2(1,3+0,3x)-0,6
0,3x+0,6= 2,6+0,6x-0,6
-0,3x=1,4
x=-14/3

0,1(x+1)-0,05(3x-10)=0,4-0,35x
0,1x+0,1-0,15x+0,5=0,4-0,35x
0,25x+0,6=0,4-0,35x
0,6x=-0,2/:0,6
x= -1/3